Kirkwood–Salzburg equation for connected correlation functions - Rebenko, O.; Pogorelov, Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
An infinite system of nonlinear Kirkwood-Salzburg equations is deduced for the connected correlation functions of a continuous system of classical point particles interacting via a pair potential. We consider the equation for density that takes into account only 2-particle correlations between the particles. The qualitative analysis of the behavior of this equation is carried out from the viewpoint of finding possible critical points indicating the existence of phase transitions for different values of temperature and chemical potential. As a possible next step, we can mention the application of numerical methods and higher correlations.